Robotic Central Hepatectomy for the Treatment of Gallbladder Carcinoma. Outcomes of Minimally Invasive Approach. Issue 3 (March 2022) - Sucandy, Iswanto; Jabbar, Furrukh; Syblis, Cameron; Crespo, Kaitlyn; Ross, Sharona; Rosemurgy, Alexander
Gallbladder cancer (GBC) is an uncommon but very aggressive malignancy with poor prognosis. Concerns for oncological inferiority related to the technical difficulties in performing laparoscopic portal lymphadenectomy discourage many surgeons to undertake this operation minimally invasively. With wide application of robotic technology to solve limitations of conventional laparoscopy, we describe our initial outcomes of robotic central hepatectomy and portal lymphadenectomy for gallbladder carcinoma in 15 consecutive patients. Data were presented as median (mean ± SD). Patients were 70 (73 ± 10.9) years old with BMI of 26 (26 ± 3.6) kg/m 2 . Tumor size was 3(4 ± 1.9) cm. Operative duration was 222 (237 ± 85.7) minutes and estimated blood loss was 200 (222 ± 135.4) mL. There were no intraoperative complications and complete resection (R0) was obtained in nearly all patients. Postoperative complications were seen in two patients (bile leak (n = 1) and respiratory failure (n = 1)). Length of stay was 3 (4 ± 4.0) days without 30-day mortality. Robotic approach is safe and effective for the treatment of GBC.